People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper analyzes Hong Kong Special Administrative Region (SAR) banks' exposure to nonbanking businesses in Mainland China. Hong Kong SAR banks are generally less exposed to riskier Mainland businesses. Despite that, a sharp deterioration in the balance sheet of Mainland businesses, as well as a sharper-than-expected downturn in the Mainland economy could negatively affect Hong Kong SAR banks, raising debt at risk well above suggested estimates. As Hong Kong SAR banks generally have sizable buffers against downside risks, the best approach to such a scenario is vigilance, including maintaining high origination and underwriting standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet